?COMPUTER AIDED DESIGN OF OVERHEAD CRANE IN HEAVY MECHANICAL COMPLEX (Biological Sciences - PJSIR, 1999)
HMCis playing vital role in country-wide proliferation of the technology.It is involved in designing and manufacturingof various plants and heavy machinery. Cranes are also included in the HMC manifold. This paper explains themethodology of converting the conventional design process of overhead cranes to Computer Aided Design (CAD),software engineering approach and the usage of different tools in order to get a computer based solution for the designof overhead cranes. Applications of parametric design and design for manufacturing concepts may also be seen. Themain idea is to automate the drafting process by linking it to design and analysis phase.